1986
DOI: 10.1002/bip.360250907
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemistry of peptides containing 1‐aminocyclopentanecarboxylic acid (Acc5): Solution and solid‐state conformations of Boc‐Acc5‐Acc5‐NHMe

Abstract: SynopsisThe conformational analysis of a protected homodipeptide of 1-aminocyclopentanecarboxylic acid (Acc5) has been carried out. 'H-nmr studies establish a p-turn conformation for Boc-Acc'. Acc'-NHMe in chloroform and dimethylsulfoxide solutions involving the methylamide NH in an intramolecular hydrogen bond. Supportive evidence for the formation of an intramolecular hydrogen bond is obtained from ir studies. X-ray diffraction studies reveal a type I11 p-turn conformation in the solid state stabilized by B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 18 publications
3
24
0
Order By: Relevance
“…77 Crystal structure determinations of short Ac 6 c containing peptides quickly con®rmed this expectation. 77±79 Helical conformations were also demonstrated in structure determinations involving Ac 5 c, 80,81 and Ac 7 c 82 peptides. The Ac n c residues appear predominantly to be limited to helical conformations.…”
Section: 76mentioning
confidence: 91%
“…77 Crystal structure determinations of short Ac 6 c containing peptides quickly con®rmed this expectation. 77±79 Helical conformations were also demonstrated in structure determinations involving Ac 5 c, 80,81 and Ac 7 c 82 peptides. The Ac n c residues appear predominantly to be limited to helical conformations.…”
Section: 76mentioning
confidence: 91%
“…"-dialkylated residues with linear substituents, like Ca~a-dimethylglycine or a-aminoisobutyric acid (Aib) (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), Capa-diethylglycine (Deg) (5,10,17), and Ca9-di-n-propylglycine (Dpg) (5,10,18), relatively few studies have been reported on peptides containing l-aminocycloalkane-I-carboxylic acids (Accn, where n is the number of carbon atoms in the cycloalkane ring). Recent X-ray diffraction investigations in our laboratory suggest that both l-aminocyclohexane-1-carboxylic acid (Acc6) (19)(20)(21)(22) and l-aminocyclopentane-I-carboxylic acid (Acc5), earlier referred to as cycloleucine and abbreviated as Cle, Cyl, cycloLeu or cLeu (23) strongly prefer folded backbone conformations in the 310/ahelical region of the conformational space (@ = k 6 0 f 20°, $ = k 30" 2 20") (24).…”
Section: Introductionmentioning
confidence: 99%
“…As a part of a program aimed to a detailed investigation of the conformational properties of the AccS residue (23), in this report we describe the X-ray diffraction structures of six Acc5 derivatives, namely Z-Acc5-OH (1) (Z, benzyloxycarbonyl), Z-ACC~-OH acetone hemi-solvate (2), Fmoc-AccS-OH (3) (Fmoc, fluoren-9-ylmethyloxycarbonyl), mC1Ac-Acc5-OH (4) o or part 187: see ref. 1. 2Author to whom correspondence may be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of both C h -hydrogens in Gly peptides by alkyl moieties has profound structural consequences. The inherent interest in peptides rich in Aib (Figure 1), the prototypical C h,h symmetrically disubstituted glycine, results not only from the restricted conformational space that this residue is allowed to explore but also from its propensity to adopt a set of , backbone torsion angles typical of regular type-III (III%) i-bend [6 -8] and 3 10 /h-helices [9]. In this connection, it was also shown that the conformational behaviour of the cycloaliphatic sub-family of the C h,h -symmetrically disubstituted Gly residues, generally referred to as Ac n c (for the medium-sized ring Ac 5 c residue, Figure 1, see References [10][11][12][13][14]), closely parallels that of Aib.…”
mentioning
confidence: 99%
“…The inherent interest in peptides rich in Aib (Figure 1), the prototypical C h,h symmetrically disubstituted glycine, results not only from the restricted conformational space that this residue is allowed to explore but also from its propensity to adopt a set of , backbone torsion angles typical of regular type-III (III%) i-bend [6 -8] and 3 10 /h-helices [9]. In this connection, it was also shown that the conformational behaviour of the cycloaliphatic sub-family of the C h,h -symmetrically disubstituted Gly residues, generally referred to as Ac n c (for the medium-sized ring Ac 5 c residue, Figure 1, see References [10][11][12][13][14]), closely parallels that of Aib. By contrast, the fullyextended C 5 conformation [7,[15][16][17] is markedly favoured over the folded/helical structures when two side-chain C i atoms are symmetrically substituted but not interconnected in a cyclic system (for the DFg residue, Figure 1, see References [18 -22]).…”
mentioning
confidence: 99%